Impact of oxLDL on Cholesterol-Rich Membrane Rafts. (20th December 2010) - Levitan, Irena; Shentu, Tzu-Pin
Abstract : Numerous studies have demonstrated that cholesterol-rich membrane rafts play critical roles in multiple cellular functions. However, the impact of the lipoproteins on the structure, integrity and cholesterol composition of these domains is not well understood. This paper focuses on oxidized low-density lipoproteins (oxLDLs) that are strongly implicated in the development of the cardiovascular disease and whose impact on membrane cholesterol and on membrane rafts has been highly controversial. More specifically, we discuss three major criteria for the impact of oxLDL on membrane rafts: distribution of different membrane raft markers, changes in membrane cholesterol composition, and changes in lipid packing of different membrane domains. We also propose a model to reconcile the controversy regarding the relationship between oxLDL, membrane cholesterol, and the integrity of cholesterol-rich membrane domains.